The Influence of Smoking Behavior on Dopamine Level Increase in the Blood of Active and Passive Smokers at Kwala Bekala Market, Medan - Chaidara; Sondang Pintauli; Kintoko Rochadi (Dentika: Dental Journal, 2024)
Cigarette is responsible for the death of 6 million people worldwide each year, with approximately 600,000 deaths related to exposure to secondhand smoke (World Health Organization (WHO)). A molecular biomarker in smoking behavior is the high level of dopamine in the blood. Therefore, this study aimed to analyze the differences in the blood dopamine levels between active and passive smokers. This comparative study consisted of 80 respondents, comprising 40 active and 40 passive smokers. The blood samples of 3 cc were taken from the vein and taken to the laboratory for measurement of dopamine level using the ELISA method. The results showed that the average dopamine level in active smokers was higher, at 70.48±21.89, while passive smokers at 65.98±25.30, with an average difference of 4.5 pg/ml. This suggested that smoking behavior could influence dopamine level in the blood of both active and passive smokers. Consequently, public awareness should to be raised about the health impacts of smoking, and the enforcement of smoking bans in public places such as Smoke-Free Areas (KTR/KUTARO) was essential to protect others from the dangers of exposure to cigarette smoke.